The complete New York Clipper baseball biographies : more than 800 sketches of players, managers, owners, umpires, reporters and others, 1859-1903 - Caillault, Jean-Pierre (McFarland & Co., 2009)
"The New York clipper was the standard bearer of sports weeklies during the 19th century featuring a weekly biographical portrait of a sporting figure. More than 800 baseball players, managers, owners, umpires, and writers were portrayed. These biographies are collected in alphabetical order, with more than 600 line-art drawings. The book features a foreword by John Thorn"--Provided by publisher